Rights and capabilities: Reading the Philippines Magna Carta of Women from the perspective of the capabilities approach - Marina Durano (University of the Philippines, School of Economics (UPSE), 2014)
The Magna Carta of Women (R.A. 7910) is the Philippines comprehensive women's human rights law. The Magna Carta of Women is found to be consistent with Rawlsian notions of justice, particularly when it undertakes inequality evaluation in primary goods. Identity-based inequality evaluation is also present in the Magna Carta of Women as implied in its definition of discrimination and marginalization. With the state as the primary duty bearer, the Magna Carta of Women gives prominence to an instrumental view of agency since participation is mediated through state mechanisms and institutions. The Magna Carta of Women fails to acknowledge the contributions of care work and the implications of the gendered division of labor. The capabilities approach highlights the challenges attached to these observations. Where human rights are viewed as ethical demands, the MCW succeeds in giving attention to aspects of women's lives that require state support.
Keywords: K3; O01; J16; K00; D63; I31; 330; gender equality; law and economics; human rights; capabilities